Youth Existence and Radicalism in Aceh, Indonesia - Ilyas, Mukhlisuddin; Ismail, Zahrila; Abdullah, Muhammad Adli; Zulfidar, Fitri (Jurnal Ilmiah Peuradeun, 2020)
In general, the discourse on youth existence and radicalism in Aceh has been started by a radicalism map and ended by analyzing data on youth involvement in countering radicalism in Aceh. The data were presented from previous facts, media publications, interviews, and observations of various sources. The result of the analysis revealed that the intensity of radicalism discourse among youth had increased in 2017. It was the momentum of the development of radicalism discourse. It was reflected by the involvement of youth activists of various community, youth and university organizations in countering radicalism ideas in Aceh. Therefore, the challenge of youth existence in responding to religious radicalism unemployment and drug in Aceh is very important. It is perceived that not every single radical action reflects the ideological belief but due to social and political gaps.